Pneumomediastinum following intubation in COVID‐19 patients: a case series. (11th June 2020) - Wali, A.; Rizzo, V.; Bille, A.; Routledge, T.; Chambers, A.J.
Abstract: The number of patients requiring tracheal intubation rose dramatically in March and April 2020 with the COVID‐19 outbreak. Our thoracic surgery department has seen an increased incidence of severe pneumomediastinum referred for surgical opinion in intubated patients with COVID‐19 pneumonitis. Here we present a series of five patients with severe pneumomediastinum requiring decompression therapy over a 7‐day period in the current COVID‐19 outbreak. We hypothesise that the mechanism for this is the aggressive disease pathophysiology with an increased risk of alveolar damage and tracheobronchial injury, along with the use of larger‐bore tracheal tubes and higher ventilation pressures. We present this case series in order to highlight the increased risk of this potentially life‐threatening complication among the COVID‐19 patient cohort and offer guidance for its management to critical care physicians.